Legal regulation of food security in the EU - Golovko, L. О. (НУБіП України, 2019)
By signing the Association Agreement with the European Union on June 27, 2014, Ukraine has continued process of adaptation of its legislation in the field of food safety to European standards. A large part of the Association Agreement is devoted to the safety of food products and sanitary and phytosanitary measures. According to Chapter 4 «Sanitary and Phytosanitary Measures» of the Association Agreement, Ukraine should introduce an equivalent European system for monitoring the quality and safety of food products. The benefits for Ukraine after signing the Association Agreement are unconditional, but more important is to implement its provisions. The methods of comparative, analytical and logical analysis were used. Taking part in the project 575523-EPP-1-2016-1-UAEPPJMO-MODULE «EU Environmental Policy and Law» we have studied European standards in the field of food security. General principles of legal regulation of food safety in the EU were analyzed. The state of adaptation of Ukrainian legislation to the requirements of the European Union law in the field of food safety was investigated. Some gaps in Ukrainian legislation were found.
Правове регулювання харчової безпеки в ЄС
Підписавши Угоду про асоціацію з Європейським Союзом 27 червня 2014 р. Україна продовжила процес адаптації вітчизняного законодавства у сфері безпеки харчових продуктів до європейських стандартів. Значна частина Угоди про асоціацію присвячена безпеці харчових продуктів і санітарним та фітосанітарним заходам. Відповідно до розділу 4 «Санітарні та фітосанітарні заходи» Угоди про асоціацію Україна повинна запровадити еквівалентну європейську систему моніторингу якості та безпеки харчових продуктів. Переваги для України після підписання Угоди про асоціацію є безумовними, але важливішим є виконання її положень. Використовувались порівняльний, аналітичний та логічний методи. Беручи участь у проекті 575523-EPP-1-2016-1-UAEPPJMO-MODULE «Екологічна політика та право в ЄС», ми вивчили європейські стандарти в галузі продовольчої безпеки. Проаналізовано загальні принципи правового регулювання безпеки харчових продуктів в ЄС. Досліджено стан адаптації українського законодавства до вимог законодавства Європейського Союзу у сфері безпеки харчових продуктів. Виявлено деякі прогалини в законодавстві України.
Keywords: food safety; EU law; sanitary and phytosanitary measures; безпека харчових продуктів; законодавство ЄС; санітарні та фітосанітарні заходи